2014
DOI: 10.2147/ijgm.s62819
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease from atrial fibrillation in adults from seven countries in Latin America

Abstract: BackgroundWhile some international studies have published epidemiologic overviews of atrial fibrillation (AF) for the Latin America region, detailed data at the national level are lacking. The aim of this study was to estimate the burden of disease and morbidity associated with AF in adults over 40 years of age in Argentina, Brazil, Chile, Colombia, Mexico, Peru, and Venezuela.MethodsNational health care system databases for each country in the analysis were used to identify cases of AF during 2010 based on IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 30 publications
0
33
0
5
Order By: Relevance
“…37 In a survey of seven countries in Latin America, more than half of the patients with atrial fibrillation were receiving medical treatment, but a significant proportion of the 60% treated as outpatients were not receiving appropriate anticoagulant therapy, despite having a high stroke risk. 18 Moreover, the proportion of patients with atrial fibrillation receiving treatment within the national healthcare system decreased with increasing age across all countries. Cost and lack of health infrastructure are major barriers to care, and suboptimal care is associated with poor outcomes.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
See 2 more Smart Citations
“…37 In a survey of seven countries in Latin America, more than half of the patients with atrial fibrillation were receiving medical treatment, but a significant proportion of the 60% treated as outpatients were not receiving appropriate anticoagulant therapy, despite having a high stroke risk. 18 Moreover, the proportion of patients with atrial fibrillation receiving treatment within the national healthcare system decreased with increasing age across all countries. Cost and lack of health infrastructure are major barriers to care, and suboptimal care is associated with poor outcomes.…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…10 The GBD 2013 survey demonstrated that stroke was among the ten leading causes of disability-adjusted life-years (DALYs) in the majority of countries in Latin America and the Latin Caribbean, and was one of the five leading causes in most of them. 18 Atrial fibrillation is more common with increasing age:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Lifestyle-related diseases account for a significant health burden in the region, including cardiovascular disease, which is now the leading cause of death and disability among adults. 19 The average population age is also rising, leading to an elevated chronic disease burden and a heightened demand on national health systems. 20 Thus, the focus of health care resource allocation has shifted from communicable disease towards non-communicable, lifestyle-related disease in recent decades and the chronic management of these conditions.…”
Section: Methodsmentioning
confidence: 99%
“…La prevalencia de FA en Latinoamérica es similar a la reportada en grandes estudios epidemiológicos. Se estima que afecta a 1,6% de la población global, variando desde 0,4% en edades menores de 50 años hasta 8,26% sobre la edad de 80 años, con 75% de casos observados en adultos mayores de 60 años 4 . La información sobre las características de pacientes con FA no valvular chilenos es escasa.…”
unclassified